Fiscal Policy Management in an Open Capital Regime - Heller, Peter (IMF Working Papers; Working Paper ;, 1997)
This paper argues that as countries open their capital regimes, the appropriate fiscal stance should become more conservative than when capital is immobile. Further fiscal adjustment may be necessary in the face of large and volatile capital flows. However, the required changes would be smaller. If a fiscal response is unavoidable, some elements of fiscal policy are easier to manipulate and less distortive than others. Determining the actual stance of fiscal policy is more difficult in an open capital regime, underscoring the need for transparency about fiscal rules. A more open capital environment also constrains the sustainable fiscal structure.